Fucoxanthin bioavailability from fucoxanthin-fortified milk: In vivo and in vitro study. (30th August 2018) - Mok, Il-Kyoon; Lee, Jae Kwon; Kim, Jeong Hwa; Pan, Cheol-Ho; Kim, Sang Min
Highlights: FX-SM showed the highest organ tissue accumulation and plasma absorption. Higher bioaccessibility and cellular uptake efficiency of FX-SM increased FX bioavailability. Higher protein and Ca 2+ ion and lower fat accounted for the higher bioaccessibility and cellular uptake efficiency of FX-SM. Abstract: Our previous study reported the improved stability of fucoxanthin (FX) fortified in whole milk (WM) and skimmed milk (SM). In this study, in vivo and in vitro FX bioavailability were investigated using FX-fortified milk (FX-SM and FX-WM) and microalga Phaeodactylum tricornutum biomass (Pt-powder). Organ tissue accumulation of FX and its metabolites (FXOH: fucoxanthinol, AXA: amarouciaxanthin A) after repeated oral administration was in the following order: FX-SM > FX-WM > Pt-powder. In vivo pharmacokinetic study with a single oral administration also demonstrated that the absorption of FXOH and AXA was the highest for FX-SM. To reinforce the in vivo results, in vitro -simulated digestion and Caco-2 cell uptake assays were performed, which revealed that FX-SM showed the highest FX bioaccessibility (release from food matrices) and cellular uptake efficiency of FX and FXOH. In conclusion, skimmed milk was validated as an excellent food matrix for FX application in terms of stability and bioavailability.